Analyzing the determinants of share unit computation for waterfront strata-titled residential building - Adzham, Mahmud (2023)
This study explores the weightage that affects the Certificate of Share Unit Formula (SiFUS), what suitable and standard weightage shall be used, and the appropriate framework for weightage calculation for the Waterfront Strata-Titled Residential. Specifically, this study focuses on the consideration of maintenance charges in the context of Malaysia. The weightage allocation to the determinant is a matter of concern that can potentially give rise to maintenance fees in Strata development. Hence, it is imperative to implement precautionary measures to effectively mitigate the risk of introducing prejudice, which may result in unfair practices. The abovementioned practices can misguide individuals who have acquired properties, including additional waterfront parcels containing exclusive yacht berths within their boundaries. The selected research case study is situated in Iskandar Puteri, Johor. This study employed a combination of qualitative and quantitative methods to gather data and analyze the research question present. Specifically, the researchers utilized the purposive sampling method to select suitable respondents. The 12 respondents involved in this research were government (eight respondents), licensed surveyors (three respondents), developers (one respondent), and management agents (one respondent). These individuals are actively designing and developing waterfront buildings, specifically in the context of Strata. As part of their role, they are required to propose the inclusion of a fair and reasonable weightage factor in Tables 1 and 2 of the Strata Act 2015. Furthermore, the government must comprehensively evaluate the weightage system before granting the SiFUS certificate to the developer. Data obtained was then analyzed using the SPSS software, employing content analysis and the Mann-Whitney test. In particular, the Mann-Whitney test yielded significant findings. These findings were further supported by descriptive analysis and context analysis. It is important to note that the circular JKPTG/4/214, which has been implemented in Malaysia, was found to be relevant within this context. The research findings have resulted in the creation of the Certificate Share Unit Computation (SiFUS) as part of the Waterfront Strata-Titled Residential Framework. In a nutshell, the research findings have the potential to bring about a significant and profound effect by materializing a revolutionary resort-style environment that seamlessly integrates with a residential community, complemented by the inclusion of a luxurious marina facility. The distinctive setting strives to create a perception of selectiveness while promoting social integration and sustainable durability.